The Social Realities of Tausug Women in Tausug Contemporary Kalangan - Sharifa Sittie Zehanie Kabirun (RIRAI Publisher, 2024)
Tausugs, one of the Muslim tribes in the Philippines, express themselves through their kalangan (songs). To explore the rich and vibrant colors of the Tausug culture, this qualitative research study employed a descriptive-analytic approach in the analysis and interpretation of thirty-one (31) Tausug Contemporary Kalangan. Through Norman Fairclough’s Critical Discourse Analysis (CDA), this study revealed and discussed the literary devices evident as a textual practice in the select kalangan; the social realities about Tausug women that were being communicated by these literary devices; and the perceptions of Tausug women about their social realities. The findings revealed that there was a total of five (5) literary devices evident as a textual practice in the select kalangan. These literary devices paved way to unveiling and explaining the social realities of Tausug women evident in the select kalangan. Despite the rich and colorful cultures of the Tausugs, the social realities of Tausug women prove that a social problem exists in the Tausug society hence must be addressed and resolved. This study proved to be an original contribution to feminist studies aimed at gaining liberation and empowerment for Tausug women.